1q24 deletion syndrome. Two cases and new insights into genotype-phenotype correlations - Lefroy, H; Fox, O; Javaid, M; Makaya, T; Shears, D (Wiley, 2018)
1q24q25 deletions cause a distinctive phenotype including proportionate short stature, microcephaly, brachydactyly, dysmorphic facial features and intellectual disability. We present a mother and son who have a 672 kb microdeletion at 1q24q25. They have the typical skeletal features previously described but do not have any associated intellectual disability. We compare the genes within our patients' deletion to those in the deletions of previously reported cases. This indicates two genes that may be implicated in the intellectual disability usually associated with this deletion syndrome; PIGC and C1orf105. In addition, our cases provide supporting evidence to recent published work suggesting that the skeletal features may be linked to the microRNAs miR199 and miR214, encoded within intron 14 of the Dynamin-3 gene.